THE IMPACT OF PRICING AND SERVICE QUALITY ON THE IMAGE OF LP3I MAKASSAR POLYTECHNIC FROM STUDENTS' PERSPECTIVE - Muh Yasin Noor; Haeruddin, Haeruddin; ImranTahalua, ImranTahalua; Syafrimansyah, Syafrimansyah (JPIM (Jurnal Penelitian Ilmu Manajemen), 2024)
This study aims to explore the relationship between pricing, service quality, and institutional image among students at Makassar Polytechnic LP3I. Utilizing a quantitative approach with Structural Equation Modeling (SEM) based on Partial Least Squares (PLS), this research analyzed data from 91 randomly selected students. The results indicate that both pricing and service quality have a significant impact on the institutional image. Clear and rational pricing strategies, as well as high-quality services, positively contribute to the institutional image, enhancing students' perception of the institution's reputation. This study emphasizes the importance of price transparency and quality service in shaping a positive institutional image and attracting prospective students. Furthermore, the study suggests the need for future research to explore the long-term effects of these factors on student satisfaction and loyalty. This research provides practical insights for policymakers and educational administrators to improve the reputation of institutions in the higher education sector in Indonesia, highlighting the crucial role of pricing and service quality in determining institutional image.